Aproximación o amenaza de la inteligencia artificial en la práctica de propiedad industrial y en sus principales actores - Romero, Margarita (2025)
The article discusses the historical presence of artificial intelligence (AI) in the world, focusing on the concerns surrounding generative artificial intelligence from an Intellectual Property perspective. It explores various applications of this technology that promise to enhance efficiency and creativity for professionals, particularly in the legal field. Furthermore, it examines aspects of Intellectual Property, such as copyright and data protection, that AI is transforming, and which exceed current legislation. Finally, the author reflects on the current realities in the defense of Intellectual Property rights at both regional and global levels.